Effect of Solanum melongena peel extract in the treatment of arsenic-induced Bowen’s disease (Bangladesh Journal of Pharmacology, 2018)
The aim of this study was to see the effectiveness of Solanum melongena peel extract in the treatment of arsenic-induced Bowen’s disease. In total 8 patients of arsenic-induced Bowen’s disease were selected from the two arsenic-endemic areas. The peel extract containing ointment was provided to each patient and instructed him/her to apply twice daily on the site of the lesion for 12 weeks. The measurement of the lesion size as well as photograph were collected both before and at the end of the study. The mean (± SD) diameter of the lesion was 3.8 ± 1.9 cm which reduced to 2.5 ± 1.7 cm (reduction 34%). The result was statistically significant.